Prevalencia de enteropatía proliferativa porcina y caracterización histopatológica de las lesiones asociadas en cerdos sacrificados en el Matadero Municipal de Medellín, Colombia (2004)
ABSTRACT: With the aim of find the prevalence of porcine proliferative enteropathy in the state-like of Antioquia, characterize its associated anatomo-pathologic lesions and to determine the etiological agent Lawsonia intracellularis. 360 intestinal tracts were evaluated at the abattoir of the municipality of Medellín, Colombia. This study took place between July to October of the year 1997. The sample calculation was obtained from a tabular infinite population with a confidence level of 95% with an error of ± 5%. All samples were gross inspected and then histologically processed by two types of stains, Hematoxiline-Eosine and Warthin-Starry. The analyses of these results were done by descriptive statistics and chi-square contingency tables. The prevalence of PPE was 87.22%, by the recognition the associated lesions caused by Lawsonia intracellularislike organisms. The most frequent lesion forms were intestinal adenomatosis 74.72%, and regional ileitis (20.55%). This paper discusses the epidemiological and pathologic findings of PPE of this region. For this reason, it constitutes the first report by a direct method in Colombia that diagnoses the presence of L intracellularis like bacterium.